Prevalence, outcomes, costs, and treatments of a contemporary population with chronic kidney disease in Norway: a nationwide observational study - Trond Geir Jenssen; Johan Bodegård; Kari Anne Sveen; Marcus Thuresson; Kåre I. Birkeland (BMC Nephrology)
Abstract Background This nation-wide study describes patients with diagnosed chronic kidney disease (CKD), with and without type 2 diabetes (T2D). Methods Prevalence, key adverse outcomes, health care costs, and use of kidney-protective treatment, up until December 31st, 2022, were described in patients aged > 18 years in Norway using register-based data. Only diagnosis codes were used to identify patients with CKD, with laboratory measurements of estimated-glomerular filtration rate and albuminuria unavailable. Utilisation of sodium-glucose cotransporter-2 (SGLT-2) inhibitors and renin-angiotensin system [RAS] inhibitors were evaluated in new users following the first Norwegian approval of an SGLT-2 inhibitor for CKD treatment. Results Approximately 3% (125,163 patients) of adults in Norway had diagnosed CKD (average age 70 years, 42% women, 73% without T2D). When describing patients with or without T2D, history of heart failure (22% versus 22%), atherosclerotic cardiovascular disease (ASCVD; 57% versus 51%), and atrial fibrillation (24% versus 27%) were similar. Larger proportions of those with T2D received SGLT-2 inhibitors (24% versus 4%) and/or RAS inhibitors (63% versus 47%). Hospitalisations for CKD (28.1 versus 22.1 events per 100 patient years), heart failure (12.6 versus 9.8), myocardial infarction (3.9 versus 2.2), and stroke (3.2 versus 2.3) were more common in patients with CKD and T2D than those without T2D. However, mortality (10.8 versus 8.5) was higher in patients without T2D. CKD and heart failure costs were higher than those for ASCVD, and generally higher in patients with T2D. SGLT-2 inhibitor utilisation increased two-fold the year after its approval but was still low, used mostly at its highest target dose. Discontinuation rates were lower with SGLT-2 inhibitors than with RAS inhibitors, the latter mostly utilised at low doses. Conclusions A CKD diagnosis was associated with substantial morbidity and mortality, costs, and undertreatment, both in patients with and without T2D. Use of novel kidney-protective treatment has increased, but an urgent need to improve the utilisation of kidney-protective medications remains, particularly in patients without T2D. Clinical trial number Not applicable.